Pseudo-2D modelling of heat redistribution through H2 thermal dissociation/recombination: consequences for ultra-hot Jupiters. Issue 3 (5th May 2021) - Roth, A; Drummond, B; Hébrard, E; Tremblin, P; Goyal, J; Mayne, N
ABSTRACT: Thermal dissociation and recombination of molecular hydrogen, H2, in the atmospheres of ultra-hot Jupiters (UHJs) has been shown to play an important role in global heat redistribution. This, in turn, significantly impacts their planetary emission, yet only limited investigations on the atmospheric effects have so far been conducted. Here, we investigate the heat redistribution caused by this dissociation/recombination reaction, alongside feedback mechanisms between the atmospheric chemistry and radiative transfer, for a planetary and stellar configuration typical of UHJs. To do this, we have developed a time-dependent pseudo-2D model, including a treatment of time-independent equilibrium chemical effects. As a result of the reaction heat redistribution, we find temperature changes of up to ∼400 K in the atmosphere. When TiO and VO are additionally considered as opacity sources, these changes in temperature increase to over ∼800 K in some areas. This heat redistribution is found to significantly shift the region of peak atmospheric temperature, or hotspot, towards the evening terminator in both cases. The impact of varying the longitudinal wind speed on the reaction heat redistribution is also investigated. When excluding TiO/VO, increased wind speeds are shown to increase the impact of the reaction heat redistribution up to a threshold wind speed. When including TiO/VO there is no apparent wind speed threshold, due to thermal stabilization by these species. We also construct pseudo-2D phase curves from our model, and highlight both significant spectral flux damping and increased phase offset caused by the reaction heat redistribution.